2021
DOI: 10.1007/s42399-021-01059-z
|View full text |Cite
|
Sign up to set email alerts
|

False-Negative RT-PCR Findings and Double Mutant Variant as Factors of an Overwhelming Second Wave of COVID-19 in India: an Emerging Global Health Disaster

Abstract: RT-PCR is considered to be the standard gold diagnostic test for detecting COVID-19 causing SARS-CoV-2. Recent reports and recent pieces of evidence from scientific literature, however, tell a different story. There have been speculations of SARS-CoV-2 escaping the RT-PCR because of the series of mutations it has gone through. It is possible that host-dependent RNA editing and high person-to-person transmission have equipped the virus with mutations enabling it to spread faster and even evade the RT-PCR. Added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 22 publications
2
27
0
1
Order By: Relevance
“…Doctors in India intensively examined the second wave and stated that bronchoalveolar lavage done on RT‐PCR negative patients with COVID‐19 symptoms produced COVID‐19 positive results. According to a doctor quoted in the same source, 15 to 20% of COVID‐19 patients comes with the aforementioned issue, which is posing a problem for doctors 17 . In another study, a scientist said that alterations in the SARS‐CoV‐2 virus may have enabled it to evade RT‐PCR testing and that the reagents must be re‐configured immediately 18…”
Section: Discussionmentioning
confidence: 99%
“…Doctors in India intensively examined the second wave and stated that bronchoalveolar lavage done on RT‐PCR negative patients with COVID‐19 symptoms produced COVID‐19 positive results. According to a doctor quoted in the same source, 15 to 20% of COVID‐19 patients comes with the aforementioned issue, which is posing a problem for doctors 17 . In another study, a scientist said that alterations in the SARS‐CoV‐2 virus may have enabled it to evade RT‐PCR testing and that the reagents must be re‐configured immediately 18…”
Section: Discussionmentioning
confidence: 99%
“…This allows the use of any automation platform leading to the realisation of the significant benefits of automation for high throughput testing as a result of reduced errors and higher throughput. The safety and cost benefits of bulk HI, in particular by not having to use MSCs and secondary containment for automation, should help the healthcare sector improve testing and become more efficient, particularly in lower and middle income group countries 33 , 38 . The use of qPCR based testing is becoming an integral part of international travel.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other viruses, the SARS-CoV-2 virus continually mutates, thus constantly creating new variants. Numerous studies have suggested that this genetic progression and mutations resulting in several COVID-19 variants may impair the sensitivity of RT-PCR diagnostic kits, with even a few mutations resulting in a significant decrease in sensitivity and an increased number of false-negative RT-PCR results [84]. On the other hand, there is heterogeneity in the literature regarding chest-CT imaging findings amongst different variants.…”
Section: Discussionmentioning
confidence: 99%